DO ENGINEERS SHARE THEIR KNOWLEDGE? A REVIEW OF KNOWLEDGE SHARING INTENTION AMONG ENGINEERS IN THE OIL AND GAS INDUSTRY - Mustafa Ahmed Hadi Almher (Center for Study and Journal Management FTI UMI, 2022)
With the current technological advancement and the competitiveness of global markets especially with the shift to renewable energy, oil and gas companies need to double their effort to overcome the challenges. Thus, engineers in the oil and gas sector should increase their job performance to that effect. Knowledge sharing is one of the major ways through which the knowledge and skills of engineers will be upgraded and eventually increase their job performance. Therefore, this study critically reviews the term knowledge sharing and the factors that affect knowledge sharing. It also reviews some factors that influence engineers’ intention towards knowledge sharing in oil and gas firms. It identifies some knowledge sharing enablers such as a knowledge-sharing culture in an organization, human network, social relationship and trust among knowledge sharers and receivers. On the other hand, it identifies some barriers to knowledge sharing such as fear of not receiving enough recognition, lack of proper awareness regarding knowledge sharing and its benefits, lack of trust, differences in the cultural environment, lack of communication skills, lack of time, lack of interest, lack of social networks and lack of motivation are of concern, lack of technological facilities. The paper identifies attitude, subjective norm, and perceived behavioural control as elements that could influence engineers’ intention towards knowledge sharing in the oil and gas sector. Finally, the paper makes some recommendations on how to effectively share knowledge among engineers in the oil and gas industry.